ความคงทนของคอนกรีต 3 มิติ เมื่อใช้งานเป็นแบบหล่อถาวรสำหรับอาคารคอนกรีตเสริมเหล็ก - WIn Ko Ko Htet,; Daungwilailuk , Totsawat; Jansang, Kamonpun; Sonrod, Atchara (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
The construction industry is undergoing transformative sector with the advancement of Three-Dimensional Concrete Printing (3DCP). This technology offers numerous advantages that encompass reduction in labor costs, minimization in construction waste, and enhancement in construction duration. This study investigates the durability of 3DCP when used as permanent formwork for reinforced concrete (RC) structures, by focusing on chloride penetration and porosity effect. A total of 9 testing specimens that are 15cm x15cm x 15cm dimensions were prepared for both types of concrete at the age of 28 days. Six of the specimens were tested and collected data (3 specimens for casted concrete and 3 specimens for 3DPC) for chloride penetration test by submerging in 3% concentration of sodium chloride solution. Chloride penetration depth was measured and evaluated the durability results between 3DPC and conventional casted concrete. Moreover, compressive strength testing was performed for conventional concrete by using three testing samples. By examining the durability of 3DPC as permanent formwork in reinforced concrete construction, this study will offer the potential of utilizing 3DPC as alternative advanced construction material.